La Patrimonialisation du logement social, observatoire de l’omnipatrimonialisation fragile : le cas de Plaine Commune - Géraldine Djament (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Plaine Commune is an intermunicipality of the northern Parisian suburbs, where the heritagization of social housing can be seen as both a site of the delicate omni-heritagization paradigm and a laboratory of heritage processes that are more diverse than the dichotomy between heritagization by designation and heritagization by appropriation. This case proposes alternatives to dominant principles which tend to favor the destruction and reconstruction of social housing. In this article, we analyze three types of social housing. The garden city of Stains illustrates heritage rehabilitation carried out by heritage institutions, local institutions and residents. The Cité Renaudie de Villetaneuse corresponds to a shift in the logic of the National Urban Renewal Agency (Agence nationale pour la rénovation urbaine, ANRU), a form of compromise achieved through heritagization by expertise (that is concurrent and/or complementary to the expertise of heritage institutions), by local institutions and by entrepreneurial appropriation. The Maladrerie in Aubervilliers presents a case of heritage rehabilitation through heritagization by appropriation. Although the architecture of the latter two neighborhoods is comparable, their differing heritage trajectories allows us to relativize the role of architecture in the heritagization of social housing. The aim is therefore not only to transmit an architecture, but also a social model, as well as to improve the living conditions of the inhabitants.